PETUAH PENDIDIKAN KEWARGANEGARAAN DALAM KONTESTASI POLITIK - T Heru Nurgiansah (Fakultas Keguruan dan Ilmu Pendidikan, 2021)
The election event became the right moment in implementing democracy in the country of Indonesia. Contestants are contenders with the winners in the hearts of society. Here is the importance of citizenship education both for voters and for the figure who is running. The purpose of this research is to know the concept of citizenship education in political contestation. This method of research uses qualitative methods. The data collection techniques in these studies use observations, interviews, and literacy studies. The results of this study say that political contestation required a democratic, responsible, and participatory attitude, which all exist in the concept of citizenship education.